School and Parent Partnership in Character Education - Shafirly Aliva; Risma Rahmawati; Farhan Ramadan; Raihan Fadilah; Adi Rosadi (COMPETITIVE: Journal of Education, 2025)
This study examines the partnership between schools and parents in supporting character education at SMA Negeri 1 Cicurug. The background is the importance of developing students’ noble character, which is not only the school’s responsibility but also requires active involvement from parents. The purpose is to evaluate how collaboration between schools and parents contributes to strengthening students’ character values. This research uses a descriptive qualitative approach with a case study method, collecting data through in-depth interviews, observations, and document analysis involving teachers, parents, and school staff. Findings indicate the partnership has been well established, marked by intensive communication and joint activities supporting character building. However, challenges include differing levels of parental participation, time constraints, and lack of coordination in some activities. The conclusion emphasizes that collaboration between schools and parents plays a vital role in character education success. Continuous efforts are needed to strengthen synergy through regular communication forums, enhanced roles of school committees, and development of character education programs actively involving parents.